(NpATRIAR[ESTWO hRIMQNA aJRIKA (B:s 1893-1907 - (NtUNQN(B, (NwALERIJ gEORGIEWI^s; (NpERWOPRISTOLXNYJ sWQTOJ |^MIADZINs ((NsW(B. (N|^MIADZIN (B:s (Nb(B. (NI(B.,s, 2013)
(NpRILOV(B.: (NS(B. 724-731s
(NbIBLIOGR(B.: (NS(B. 732-745 (333 (NNAZW(B.)s
Keywords: c -- 1820-1907; (NaRMQNSKAQ aPOSTOLXSKAQ CERKOWXs; (NiSTORIQ ARMQNSKOGO NARODAs -- (NcERKOWXs -- 1893-1907 (NGG(B.s